012 Morphine requirements in paediatric live related renal transplant recipients receiving continuous transversus abdominis plane catheter. (December 2018) - Hume-Smith, H; Dobby, N; Clunies Ross, N; Young, R; Masardi, C; Kawamoto, K; Calder, F; Callaghan, C; Drage, M; Kessaris, N; Marks, S
Abstract : Introduction: Effective postoperative pain management is important following paediatric renal transplant (pRT). Currently, the mainstay of pain control at Great Ormond Street Hospital (GOSH) is opioid analgesia. A previous audit demonstrated that patients on opioid analgesia on the renal ward at GOSH have significantly more postoperative nausea/vomiting and pruritus than non-renal patients. The use of single-shot transversus abdominis plane block (TAPB) and continuous TAP (cTAP) infusions may reduce opioid consumption and related side effects. They have been shown to reduce opioid consumption in the first 24 hours post-surgery in adults (Farag E, et al . Continuous transversus abdominis plane block catheter analgesia for postoperative pain control in renal transplant. J Anesth 2015;29:1, pg 4–8) Methods: After institutional approval, an observational study was conducted of pRT recipients. A standard general anaesthetic was administered to all patients. For those receiving a cTAP infusion, a multi-orifice catheter was placed into the wound under direct vision by the surgeon. Statistical analysis was performed using Man Whitney U-test with significance level p<0.05. Results: 38 patients aged 3–17 years with end-stage kidney disease undergoing living donor RT were analysed. 10 received a cTAPB +N/PCA, 28 received TAPB+N/PCA or N/PCA only. The median dose of total postoperative opioid consumption was 1.39, 22.50 and 22.47 mcg/kg/hr in cTAPB +N/PCA, TAPB+N/PCA and N/PCA groups respectively (IQR=0.33, 4.9; 15.83, 28.00; 15.18, 37.48). A significant difference was seen in morphine consumption between TAPB+N/PCA and cTABP +N/PCA groups on D0 (p=0.00453), D1 (p=0.03515) and D2 (p=0.01578). Conclusions: The cTAPB technique shortens the duration of N/PCA use and shows promising results for reduction in opioid requirements postoperatively. Patients receiving cTAPB appeared more comfortable and used their N/PCA less.